2004
DOI: 10.1111/j.1365-3156.2004.01335.x
|View full text |Cite
|
Sign up to set email alerts
|

The practical importance of permanent and semipermanent habitats for controlling aquatic stages of Anopheles gambiae sensu lato mosquitoes: operational observations from a rural town in western Kenya

Abstract: SummaryControl of aquatic-stage Anopheles is one of the oldest and most historically successful interventions to prevent malaria, but it has seen little application in Africa. Consequently, the ecology of immature afrotropical Anopheles has received insufficient attention. We therefore examined the population dynamics of African anopheline and culicine mosquitoes using operationally practicable techniques to examine the relative importance and availability of different larval habitats in an area of perennial m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

18
236
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 201 publications
(255 citation statements)
references
References 42 publications
18
236
1
Order By: Relevance
“…gambiae olfactory system, there is a paucity of information as to the molecular and cellular basis of olfaction in larval stages, in which it may be of potential importance in disease control. Paradoxically, despite being one of the historically most successful strategies for mosquito control (2) and prevention of human malaria, the targeting of mosquito larvae or larval habitats around human dwellings is sparsely implemented in Africa and other malaria-endemic regions (3). Furthermore, the simplicity of insect larval olfactory systems makes them excellent models to study olfactory signal transduction and coding.…”
mentioning
confidence: 99%
“…gambiae olfactory system, there is a paucity of information as to the molecular and cellular basis of olfaction in larval stages, in which it may be of potential importance in disease control. Paradoxically, despite being one of the historically most successful strategies for mosquito control (2) and prevention of human malaria, the targeting of mosquito larvae or larval habitats around human dwellings is sparsely implemented in Africa and other malaria-endemic regions (3). Furthermore, the simplicity of insect larval olfactory systems makes them excellent models to study olfactory signal transduction and coding.…”
mentioning
confidence: 99%
“…Adult mosquitoes are difficult to control since they can fly relatively long distances and survive in a range of microhabitats, including houses, vegetation, holes in rocks and soil, among others (Gilles and Warrell 1993). Nevertheless, the adult stage has been the main target in mosquito control for decades (Fillinger et al 2004). Larval control has only been taken into account recently, and is still underestimated in many areas .…”
Section: Introductionmentioning
confidence: 99%
“…Mosquitoes may exploit any available water for oviposition, natural or man-made (Imbahale et al, 2011;Fillinger et al, 2004), permanent or temporary (Fillinger et al, 2004), clean or polluted (Sattler et al, 2005;Awolola et al, 2007;Chinery, 1984) and of various sizes from hoof-prints of animals to the edges of large water bodies (Sattler et al, 2005;Mutuku et al, 2006b;Imbahale et al, 2011), although individual species have preferences of habitat type. For example, Anopheles gambiae complex mosquitoes, the principal malaria vector in Sub-Sahara Africa prefer temporary, sunlit water bodies for their breeding, which become abundant during the rainy season (Mutuku et al, 2006a;Minakawa et al, 2004), although their larvae have also been found in polluted waters (Imbahale et al, 2011;Awolola et al, 2007;Sattler et al, 2005).…”
Section: Introductionmentioning
confidence: 99%